Outros olhares para outras Américas: cultura visual e fotografia na América Latina pós-tradicional - Sérgio Luiz Pereira da Silva (Ciências Sociais Unisinos)
This paper presents a reflection on the critical role and the politics behind the photographic look at the context the visual culture in Latin American. We present the photographic look as an agent of social action in the context of visual culture. The photographic documentation, as one of the main artifacts of visual culture, has the power to provide an overview, through a non-verbal communication, between the registered fact, the cut-off of the Real, and the interpretations drawn on it, creating thereby art and realism. This relation of correspondence between representation and interpretation has always been subject to the established cultural conventions, but it represents a social action of the look into a possible visual awareness. We argue that social action of the look sharpens its own centrality in the dimensions of the public sphere, in which the change of this form of representation is one way to increase the autonomy of the image in the public space, and to notice it each time more decontextualized in relation to its referent.